3Ps-Based Game for Teaching Vocabulary to Young Learners - Hakim, Abdul Malik; Egar, Ngasbun; Musarokah, Siti (Universitas PGRI Semarang, 2025)
This study highlights the importance of building strong self-regulated motivation in EFL learners before engaging them in academic writing tasks. Motivation plays a vital role in helping learners handle the challenges of academic writing and develop effective learning strategies. This small-scale library research aimed to explore how self-regulated motivation supports the improvement of EFL learners’ writing skills. A thematic analysis was conducted on 25 studies related to self-regulated motivation and academic writing to ensure the relevance and reliability of the findings. The results revealed two main outcomes: (1) self-regulated motivation helps learners become more organized in their writing process, and (2) it enables them to achieve better academic writing outcomes. These findings emphasize the need for educators to promote self-regulation in writing instruction to support learners’ long-term academic growth.